Feasibility of dendritic cell-based vaccine against glioblastoma by using cytoplasmic transduction peptide (CTP)-fused protein antigens combined with anti-PD1. Issue 11 (1st November 2020) - Kim, Young-Hee; Tran, Thi-Anh-Thuy; Duong, Thi-Hoang-Oanh; Jung, Shin; Kim, In-Young; Moon, Kyung-Sub; Jang, Woo-Youl; Lee, Hyun-Ju; Lee, Je-Jung; Jung, Tae-Young
ABSTRACT: Recent clinical trials utilizing antigen-pulsed dendritic cells (DCs) have demonstrated increased survival of vaccinated cancer patients. Besides, the cytoplasmic transduction peptide (CTP) not only has an excellent transcellular efficiency but also shows a strong tendency to remain in the cytoplasm after transduction, without migrating into the nucleus. In this study, we investigated the effectiveness of immunotherapy against malignant gliomas using DCs pulsed with CTP-fused protein antigens combined with programmed cell death protein 1 blockade (anti-PD1). The expression of tumor associated antigen (WT1 and BIRC5) and PDL1 on glioblastoma (GBM) target cells was confirmed by western blot. The effect of CTP-fused protein antigens on mature DCs (VaxDCs) was determined. The immunophenotypes of VaxDCs pulsed with CTP-fused protein antigens was confirmed by flow cytometry and the cytokine production levels of T helper polarization were measured by enzyme-linked immunosorbent (ELISA) assay. The IFN-γ-enzyme linked immunospot and lactate dehydrogenase release assays were performed to estimate the cytotoxic activity of antigen-specific cytotoxic T lymphocytes (CTLs), stimulated by VaxDCs pulsed with CTP-fused protein antigens and anti-PD1, against malignant glioma cells expressing target antigens. VaxDCs pulsed with CTP-fused protein antigens showed enhanced expression of major histocompatibility complex (MHC) and co-stimulatory markers of DCs and resulted in Th1 cytokine polarization. The increase in the number of IFN-γ + effector T cells paralleled with the enhanced percent specific lysis of GBM targets cells by antigen-specific CTLs. Our study suggested that using CTP-fused protein antigens for DC vaccine preparation along with PD1 blockade could be an effective immunotherapy strategy for GBM.